2022
DOI: 10.1371/journal.ppat.1010322
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus infection is regulated by NPC1 and endosomal cholesterol homeostasis

Abstract: Cholesterol homeostasis is required for the replication of many viruses, including Ebola virus, hepatitis C virus, and human immunodeficiency virus-1. Niemann-Pick C1 (NPC1) is an endosomal-lysosomal membrane protein involved in cholesterol trafficking from late endosomes and lysosomes to the endoplasmic reticulum. We identified NPC1 in CRISPR and RNA interference screens as a putative host factor for infection by mammalian orthoreovirus (reovirus). Following internalization via clathrin-mediated endocytosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 87 publications
(134 reference statements)
2
9
0
Order By: Relevance
“…4C). This non-monotonic dependence of GUV rupture on the cholesterol content is qualitatively consistent with previous reports that either depletion [30,31] or overly accumulation [32] of cholesterol blocked the infectivity of non-enveloped viruses. Further, we found that when the ISVP concentration was increased to 300 pM, both T1L and T1L/T3DM2 strains caused the rupture of nearly all GUVs containing 7.7 mol% cholesterol.…”
Section: Cholesterol Enhances Isvp-induced Membrane Disruptionsupporting
confidence: 92%
See 1 more Smart Citation
“…4C). This non-monotonic dependence of GUV rupture on the cholesterol content is qualitatively consistent with previous reports that either depletion [30,31] or overly accumulation [32] of cholesterol blocked the infectivity of non-enveloped viruses. Further, we found that when the ISVP concentration was increased to 300 pM, both T1L and T1L/T3DM2 strains caused the rupture of nearly all GUVs containing 7.7 mol% cholesterol.…”
Section: Cholesterol Enhances Isvp-induced Membrane Disruptionsupporting
confidence: 92%
“…It is known that cholesterol levels play a significant role in viral infections [29] . Depleting cholesterol was shown to block cell entry of non-enveloped viruses such as adenovirus and poliovirus [30,31] , while cholesterol accumulation in endosomes also impairs reovirus escape [32] . It was proposed that membrane cholesterol level might influence either ISVP-to-ISVP* conversion or membrane disruption by reovirus [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the Niemann-Pick C1 (NPC1), which is a transmembrane protein that mediates the exportation of cholesterol from late endosomes and lysosomes. According to a recent study, NPC1-mediated cholesterol transport is required for MRV penetration from the late endosome into the cytoplasm, but not for MRV attachment, internalization, or uncoating ( Ortega-Gonzalez et al, 2022 ). In the present study, we preliminarily investigated the potential inhibition mechanism of 25HC against ARV at the viral entry stage.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 It remains unclear how cholesterol affects reovirus interaction with membranes, but studies suggested that membrane cholesterol level influences either ISVP-to-ISVP* conversion or membrane disruption by reovirus. 38 In our experiments, we prepared GUVs with varying amounts of cholesterol, from 0% (DOPC: DOPE = 2:1 molar ratio), 7.7 mol % (DOPC:DOPE: cholesterol = 8:4:1), 14.3 mol % (DOPC:DOPE: cholesterol = 4:2:1), to 25.0 mol % (DOPC:DOPE: cholesterol = 2:1:1), comparable to the endosomal cholesterol level. 39−41 After adding 10 pM of either T1L or T1L/T3DM2 ISVPs to the GUVs, we observed more ISVPs adhered to the membranes containing cholesterol and formed larger aggregates compared to that on membranes without cholesterol.…”
Section: Live-cell Imaging Of Endosomal Deformationmentioning
confidence: 99%